2007
DOI: 10.1152/ajpheart.00976.2006
|View full text |Cite
|
Sign up to set email alerts
|

p22phox in the macula densa regulates single nephron GFR during angiotensin II infusion in rats

Abstract: Angiotensin II (ANG II) infusion increases renal superoxide (O(2)(-)) and enhances renal vasoconstriction via macula densa (MD) regulation of tubuloglomerular feedback, but the mechanism is unclear. We targeted the p22(phox) subunit of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) with small-interfering RNA (siRNA) to reduce NADPH oxidase activity and blood pressure response to ANG II in rats. We compared single nephron glomerular filtration rate (SNGFR) in samples collected from the proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…This reflects NO bioinactivation by O 2 -in the JGA of the SHR. In other studies, systemic silencing of the p22 phox gene during ANG II infusion reduced renal ROS, and prevented progressive hypertension (191) and moderated the TGF responses (207). Fu et al (70) reported that activation of AT1R by ANG II mediated NOX2-dependent O 2 -production in the MD cells, whereas basal O 2 -generation was sustained by NOX4.…”
Section: Tubuloglomerular Feedbackmentioning
confidence: 95%
See 4 more Smart Citations
“…This reflects NO bioinactivation by O 2 -in the JGA of the SHR. In other studies, systemic silencing of the p22 phox gene during ANG II infusion reduced renal ROS, and prevented progressive hypertension (191) and moderated the TGF responses (207). Fu et al (70) reported that activation of AT1R by ANG II mediated NOX2-dependent O 2 -production in the MD cells, whereas basal O 2 -generation was sustained by NOX4.…”
Section: Tubuloglomerular Feedbackmentioning
confidence: 95%
“…phox was required for salt-sensitive hypertension (62), p22 phox and p47 phox for ANG II-induced hypertension (103,153,191,207) and for genetic hypertension in spontaneously hypertensive rats (SHR) (29, 265), and Poldip2 for hypertension in models of chronic kidney disease (CKD) (150).…”
Section: Overview Of Renal Ros and Hypertensionmentioning
confidence: 99%
See 3 more Smart Citations